Glomus Tumor of the Face: A Case Report and Literature Review - Maurya, Sanjay; Wadhwa, Sumedha; Singh, Onkar; Bhatt, Peeyush (Indian Journal of Plastic Surgery, 2025)
Glomus tumors are benign mesenchymal neoplasms arising from the glomus body. The most common site of presentation of a glomus tumor is the subungual region, followed by the fingertip and foot. Facial glomus tumors are extremely rare and constitute less than 1% of all glomus tumors. We report a case of facial glomus tumor that presented with a small painful nodule on the face. Following its excision, the diagnosis of glomus tumor came as a histopathological surprise.
Keywords: facial glomus tumor; magnetic resonance imaging; extradigital glomus tumor; A-V malformation